2017
DOI: 10.1038/s41598-017-02548-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K suppresses propagation of drug-tolerant cancer cell subpopulations enriched by 5-fluorouracil

Abstract: Drug-tolerant cancer cell subpopulations are responsible for relapse after chemotherapy. By continuously exposing the gastric cancer cell line MKN45 to 5-FU for >100 passages, we established a 5-fluorouracil (5-FU)-tolerant line, MKN45/5FU. Orthotopic xenografts of MKN45/5FU cells in the stomach of nude mice revealed that these cells had a high potential to metastasize to sites such as the liver. Levels of phosphorylated phosphatidylinositide 3-kinase (PI3K) increased both in 5-FU-tolerant subpopulations accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The protein expression pattern of 5FU treatment in the present study was similar to that of EGCG treatment, which was consistent with a previous study showing that the changes caused by 5FU injection in an orthotopic xenograft of human gastric cancer cells in the gastric submucosal layer from nude mice on the protein expression of the PI3K/Akt/mTOR pathway were small [122]. Furthermore, our results suggested that EGCG could be used as anticancer agent without creating undesirable side effects for healthy organs of the tumor-bearing host.…”
Section: Discussionsupporting
confidence: 92%
“…The protein expression pattern of 5FU treatment in the present study was similar to that of EGCG treatment, which was consistent with a previous study showing that the changes caused by 5FU injection in an orthotopic xenograft of human gastric cancer cells in the gastric submucosal layer from nude mice on the protein expression of the PI3K/Akt/mTOR pathway were small [122]. Furthermore, our results suggested that EGCG could be used as anticancer agent without creating undesirable side effects for healthy organs of the tumor-bearing host.…”
Section: Discussionsupporting
confidence: 92%
“…it is widely accepted that the Pi3K/akt pathway plays an important role in drug resistance. overexpression of this Pi3K/akt pathway has been identified in 5-Fu-resistant cell lines, and the blocking of this pathway could sensitize cancer cells to 5-Fu in vitro (37). However, activation of the Pi3K/akt pathway was revealed to induce 5-Fu resistance in cancer cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K-AKT pathway is among the most important mechanisms of enhanced chemoresistance in gastric cancer [ 27 , 28 ]. Inhibition of PI3K can suppress propagation of drug-tolerant gastric cancer cell subpopulations enriched by 5-fluorouracil [ 29 ] and also strengthen their response to multiple chemotherapeutic reagents [ 30 , 31 ]. GLI1- mediated activation of PI3K/AKT pathway was observed in colorectal cancer [ 32 ], ovarian cancer [ 33 ], and hepatocellular carcinoma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%